Improving Digital Financial Literacy and Fintech Utilization among Students through Education and Mentoring Programs at Lagos State University of Education Nigeria - Agoi, Moses Adeolu; Oshinowo, Oluwakemi Racheal; Asipah, Asipah (Dharmahita: Journal of Community Service and Development, 2026)
This community service program aimed to enhance digital financial literacy and promote the responsible use of financial technology (FinTech) among university students at Lagos State University of Education, Nigeria. The primary objective was to empower students with essential knowledge, skills, and ethical awareness needed to navigate digital financial technologies (DFINTECH) safely and effectively in their daily financial activities. The program adopted a participatory and educational-based approach that integrated capacity building, practical mentoring, and reflective evaluation. The method was implemented through four sequential stages: needs assessment, educational intervention, mentoring and practical engagement, and evaluation and reflection. The needs assessment identified students’ levels of financial literacy, patterns of FinTech usage, and key challenges related to digital security and financial decision-making. Educational interventions were delivered through interactive workshops covering budgeting, saving, responsible borrowing, FinTech services, digital security, and ethical issues. This was followed by mentoring and hands-on activities that guided students in critically evaluating and responsibly using selected FinTech applications. Program effectiveness was assessed through feedback instruments, observations, and reflective discussions. The results indicate a noticeable improvement in students’ understanding of digital financial concepts, awareness of financial risks, and confidence in using FinTech responsibly. Participants demonstrated increased critical thinking toward digital financial products and greater self-regulation in financial behavior. Overall, the program contributed positively to strengthening students’ financial resilience and promoting sustainable and ethical engagement with digital financial technologies.